ПОНЯТТЯ ТА ВИДИ ЗАХОДІВ ПРИМУСОВОГО ВИКОНАННЯ СУДОВИХ РІШЕНЬ В УКРАЇНІ, ОСОБЛИВОСТІ ЇХ РЕАЛІЗАЦІЇ - П'ятницький, Андрій Васильович (SUPREMANCE OF LAW, 2018)
In the article, on the basis of the analysis of scientifi c views of scientists and the norms of the current legislation of Ukraine, the concept and types of measures of enforcement of court decisions in Ukraine. It is stressed that the application of each of the measures under consideration to enforce court decisions in any case is a compulsory need, since only with their use it is possible to support stability in society by ensuring that each person follows a certain order in public relations.